2021
DOI: 10.32615/bp.2021.052
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in photosynthesis, phenolic content, antioxidant activity, and anatomy of apical and basal leaves of Aristotelia chilensis

Abstract: Aristotelia chilensis (Mol.) Stuntz is an evergreen species endemic to Chile. It grows in open areas or under tree canopy, and its leaves emerge in early spring and summer. The objective of this study was to determine changes in photosynthetic parameters, total phenol content (TPC), antioxidant activity, and anatomy of apical and basal leaves of A. chilensis during the year. Photosynthesis performance was determined by measuring electron transport rate (ETR), the quantum efficiency of photosystem II (Fv/Fm), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated that A. chilensis aqueous extract exhibits anti-inflammatory effects and immunomodulatory activity related to atopic-like dermatitis [ 113 ]. Several epidemiological studies on human health have underlined the beneficial role of phenolic compounds in preventing arteriosclerosis, cardiovascular diseases, arthritis, diabetes, neurodegenerative diseases, and cancers [ 113 , 114 ]. The berries have increased uses and are broadly selected to develop healthy or potential functional foods because of their biological attributes [ 110 ].…”
Section: Native Plants and Their Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that A. chilensis aqueous extract exhibits anti-inflammatory effects and immunomodulatory activity related to atopic-like dermatitis [ 113 ]. Several epidemiological studies on human health have underlined the beneficial role of phenolic compounds in preventing arteriosclerosis, cardiovascular diseases, arthritis, diabetes, neurodegenerative diseases, and cancers [ 113 , 114 ]. The berries have increased uses and are broadly selected to develop healthy or potential functional foods because of their biological attributes [ 110 ].…”
Section: Native Plants and Their Metabolitesmentioning
confidence: 99%
“…Furthermore, it has been described that this species has a high concentration of anthocyanin pigments, giving its berries a characteristic dark violet color [ 53 ]. The maqui fruit has four times more antioxidant properties than other berries [ 114 ]. A. chilensis is rich in poly-glycosylated derivatives with high antioxidant capacity, which suggests antiatherogenic properties.…”
Section: Native Plants and Their Metabolitesmentioning
confidence: 99%